2020
DOI: 10.1200/jco.19.00904
|View full text |Cite|
|
Sign up to set email alerts
|

Phase III Trial of Adjuvant Capecitabine After Standard Neo-/Adjuvant Chemotherapy in Patients With Early Triple-Negative Breast Cancer (GEICAM/2003-11_CIBOMA/2004-01)

Abstract: PURPOSE Operable triple-negative breast cancers (TNBCs) have a higher risk of relapse than non-TNBCs with standard therapy. The GEICAM/2003-11_CIBOMA/2004-01 trial explored extended adjuvant capecitabine after completion of standard chemotherapy in patients with early TNBC. PATIENTS AND METHODS Eligible patients were those with operable, node-positive—or node negative with tumor 1 cm or greater—TNBC, with prior anthracycline- and/or taxane-containing chemotherapy. After central confirmation of TNBC status by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(147 citation statements)
references
References 12 publications
3
123
2
3
Order By: Relevance
“…From these databases, HER2-negative tumors with known IHC and HER2 amplification status were extracted 10 13 . Other patients were extracted from internal databases from the Hospital Clinic (Barcelona, Spain), from two SOLTI clinical trials (SOLTI 1501-VENTANA and SOLTI 1402-CORALEEN) 14 , 15 , from the Spanish Cancer Research Group (GEICAM)/CIBOMA study 16 and from a previously published collaboration between Hospital Clinic (Barcelona, Spain), Hospital Vall d’Hebron (Barcelona, Spain), University Campus Bio-Medico (Roma, Italy) and GEICAM 17 (see Supplementary Table 9 for study details). All studies had received proper ethical approval by the local institutional research ethics committee of all participating institutions and patients had given their consent to participate.…”
Section: Methodsmentioning
confidence: 99%
“…From these databases, HER2-negative tumors with known IHC and HER2 amplification status were extracted 10 13 . Other patients were extracted from internal databases from the Hospital Clinic (Barcelona, Spain), from two SOLTI clinical trials (SOLTI 1501-VENTANA and SOLTI 1402-CORALEEN) 14 , 15 , from the Spanish Cancer Research Group (GEICAM)/CIBOMA study 16 and from a previously published collaboration between Hospital Clinic (Barcelona, Spain), Hospital Vall d’Hebron (Barcelona, Spain), University Campus Bio-Medico (Roma, Italy) and GEICAM 17 (see Supplementary Table 9 for study details). All studies had received proper ethical approval by the local institutional research ethics committee of all participating institutions and patients had given their consent to participate.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 3842 TNBC patients were included in this meta-analysis. In two of the trials, the entire cohort of patients had TNBC [ 19 , 21 ], while in the other seven trials TNBC patients were one of the subgroups. The main research features are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…There were five [ 14 , 17 19 , 21 ] and four [ 15 , 16 , 20 , 22 ] studies involving the addition or replacement of capecitabine to neoadjuvant or adjuvant chemotherapy, respectively. From the available data of TNBC, there were 1373 capecitabine combined and 1356 capecitabine-free cases in the group with the addition of capecitabine, and 384 capecitabine combined and 357 capecitabine-free cases in the group with the replacement of capecitabine.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in the preliminary results of a phase III GEICAM/CIBOMA trial, which enrolled 876 Caucasian women with early-stage TNBC treated with (neo)-adjuvant chemotherapy, the extension with adjuvant capecitabine versus placebo did not significantly improve 5-year DFS (80% vs. 77%) and OS (86.2% vs. 85.9%) in the whole study population, although in a pre-specified subgroup analysis, a significant survival benefit was reported among patients with no basal-like TNBC [66].…”
Section: Treatment Of Early Stagementioning
confidence: 88%